The Development a Polymerase Chain Reaction (PCR) to detect C.Pneumoniae and C.Psittaci - Sabagh, Fatemeh; Storey, Christopher C (Archives of Advances in Biosciences, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> C.pneumoniae and C.psittaci both cause respiratory infections in human. detection of these organisms in tissue culture is difficult and serological testing is unreliable. There are no sensitive and reliable tests for the detection of these organisms. The polymerase chain reaction (PCR ) has provided an alternative diagnostic method for the detection of these fastidious organisms. The aim of this study was to develop a PCR to detect C.pneumoniae and C.psittaci from clinical samples. The PCR was optimized in a series of experiments. To determine if the optimized PCR could be applied to clinical samples, mock positive specimen were produced by adding chlamydiae to throat swab from healthy adults. The DNA was extracted by phenol/chloroform. When tested by PCR all the throat swabs were negative. However, when diluted and retested, many of the swabs were positive and 10 IFU of C.psittaci and 100 IFU of C.pneumoniae could be detected. This experiment indicates that inhibitor to PCR are found in throat swab and further work is needed on specimen preparation. The PCR was optimized in a series of experiments. The optimal conditions were to use a two segment PCR with 68°c annealing and polymerization temperature, 2.0mM Mgcl2, 0.2μM primers and 40 cycles. The PCR was highly sensitive and could detect one inclusion forming unit with both C.pneumoniae and C.psittaci strains. Two human strains and one nonhuman strain of C.pneumoniae and two avian strains and three mammalian strains of C.psittaci were used to determine the specificity of PCR. The PCR detected all these different strains. C.trachomatis strains were not detected. Various bacterial strains, fungi DNA, and human DNA were negative in PCR and no amplification DNA was found in negative controls.